Integrative Cancer Care: Leveraging Nutrition and Positive Psychology for Optimal Outcomes - Arabmoorchegani, Maryam; Abbasi, Mahsa; Asadalizadeh, Mahya; Motavaf, Forough (Asian Pacific Journal of Cancer Nursing, 2025)
Overview: This review article examines novel approaches in cancer management, emphasizing the roles of healthy nutrition and positive psychology. In recent years, numerous studies have evaluated the effects of diets rich in antioxidants, omega-3 fatty acids, and fiber, as well as psychological interventions such as cognitive-behavioral therapy and mindfulness practices, on improving both the physical and mental well-being of cancer patients. Methods: Relevant studies were retrieved from international databases using keywords including “cancer,” “healthy nutrition,” “positive psychology,” “complementary treatment,” and “immune system.” Inclusion criteria comprised clinical articles, meta-analyses, and observational studies focusing on the impact of nutritional and psychological interventions on treatment outcomes in cancer patients. The quality of the selected studies was assessed using internationally recognized standards. Results: The findings indicate that nutritional interventions can enhance cellular metabolism, reduce inflammation, and strengthen the immune system, which may contribute to slowing tumor growth. Additionally, psychological interventions have been shown to reduce anxiety and depression, improve emotional coping, and enhance the overall quality of life in patients. Notably, integrated approaches that combine nutritional and psychological strategies addressing both physical and mental health concurrently have yielded particularly promising results. However, some studies have reported limitations, such as small sample sizes and high variability in patient populations. Conclusion: Integrating healthy nutritional strategies with psychological interventions as complementary therapies shows considerable potential for improving clinical outcomes and the quality of life in cancer patients. Future research employing more rigorous clinical designs and larger sample sizes is needed to clarify the precise role of these approaches within comprehensive cancer treatment protocols.